Structural and Thermochronologic Constraints on the Cenozoic Tectonic Development of the Northern Indo‐Burma Ranges. Issue 9 (4th September 2020) - Haproff, Peter J.; Odlum, Margaret L.; Zuza, Andrew V.; Yin, An; Stockli, Daniel F.
Abstract: The 1, 500‐km‐long, north trending Eastern Flanking Belt of the Himalayan‐Tibetan orogenic system is located along the eastern margin of the Indian subcontinent. Although the belt is a key element of the Cenozoic India‐Asia collisional zone, its tectonic evolution remains poorly understood. This lack of knowledge has impacted our ability to differentiate between competing hypotheses for the evolution of the India‐Asia collision. To address this problem, we integrate constraints on the structural framework and magnitude of Cenozoic shortening strain with thermochronology of the northernmost segment of the belt located directly southeast of the eastern Himalayan syntaxis (i.e., the northern Indo‐Burma Ranges). The study area exposes a southwest directed thrust belt that is bounded by the Indian craton in the west and the right‐slip Jiali fault zone in the east. New and existing (U‐Th)/He and 40 Ar/ 39 Ar thermochronologic data indicate that thrust‐related cooling occurred from 36 Ma in the northeast to 5.6 Ma in the southwest. Episodes of out‐of‐sequence thrusting occurred at 30–20, 14–12, and 11–6 Ma within the thrust belt. Restoration of the thrust belt yields a minimum horizontal shortening of 280 km ( 86%). These results combined with (1) the recorded local absence of several major Himalayan‐Tibetan lithologic units (i.e., Tethyan Himalayan Sequence, Greater Himalayan Sequence, and southern Gangdese batholith) and (2) the southward decrease in the thrust‐belt width (33–5 km) suggest a complex history of thrusting in the northern Indo‐Burma Ranges and an spatial increase in Cenozoic crustal shortening and/or continental underthrusting from west to east across the eastern Himalayan syntaxis. Key Points: The northern Indo‐Burma Ranges expose a Cenozoic southwest to west directed thrust belt that is bounded by two active right‐slip faults Thrusting since 36 Ma accommodated >280 km (86%) shortening during clockwise crustal flow around the eastern Himalayan syntaxis Our findings support an increase in Cenozoic shortening and/or continental underthrusting along the easternmost India‐Asia plate boundary